2022
DOI: 10.1182/blood.2021014124
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in vaccinated adult patients with hematological malignancies: preliminary results from EPICOVIDEHA

Abstract: In a Plenary Paper, Mittelman and colleagues assess the relative clinical efficacy of mRNA vaccination on COVID-19 disease incidence and outcomes in patients with hematologic malignancies compared with healthy matched controls. This population-based study from Israel links prior observations of poor serologic responses to vaccination to higher risk for breakthrough infection, hospitalization, and death in patients with blood cancer, especially those on active antineoplastic therapy. In an accompanying Letter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 22 publications
7
108
3
Order By: Relevance
“…These studies also reported cases of breakthrough infections in partially or completely vaccinated patients. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] A comprehensive workup of SARS-CoV- HM) and demonstrated a high booster-induced seroconversion of 56%, even in patients that were previously treated for their malignancy. 80 Prior BTKi or anti-CD20 treatment was associated with inferior postbooster seroconversion and anti-S IgG titers.…”
Section: Covidmentioning
confidence: 99%
“…These studies also reported cases of breakthrough infections in partially or completely vaccinated patients. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] A comprehensive workup of SARS-CoV- HM) and demonstrated a high booster-induced seroconversion of 56%, even in patients that were previously treated for their malignancy. 80 Prior BTKi or anti-CD20 treatment was associated with inferior postbooster seroconversion and anti-S IgG titers.…”
Section: Covidmentioning
confidence: 99%
“…Interestingly, this discordant response seems to be more prevalent with BNT162b2 (BioNTech, Pfizer) and not mRNA-1273 (Moderna) [ 92 ]. Despite these challenges, a significant decrease in overall mortality has been reported for patients with hematologic malignancies and COVID-19 in the postvaccination period compared to pre-vaccination at 12.4% versus 31%, respectively [ 93 ]. Recent novel developments in the use of monoclonal antibodies for pre-exposure prophylaxis in immunocompromised patients are promising.…”
Section: Covid-19 Therapeutics In Patients With Hematologic Malignanciesmentioning
confidence: 99%
“…Following title/abstract screening, 479 articles were excluded. Of the remaining 90 publications, 62 studies fulfilled the eligibility criteria and 28 were excluded due to the following reasons: eight studies were not related to our topic [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , seven studies provided not enough data in the case of seropositiviness after immunization [31] , [32] , [33] , [34] , [35] , [36] , [37] , four studies evaluated the immunogenicity of a third dose [38] , [39] , [40] , [41] , two studies were conference abstracts [42] , [43] , two studies were case reports [44] , [45] , two studies reported the cellular outcomes solely [46] , [47] , one study reanalyzed the data of the same included studies (48) , one study was a protocol of an original article (49) , and one study was commentary (50) . Furthermore, 20 additional articles were retrieved from other sources, resulting in inclusion of 82 potential studies to be included in the final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%